School-Based Management to Improve Technology-Based Mathematics Learning at Junior High Schools in Jakarta - Supadi, Supadi; Hasbullah, Hasbullah; Dalmeri, Dalmeri; Nuriah, Yuyun; Hamidah, Nur; Leonard, Leonard (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
This study aims to analyse the application of School-Based Management (SBM) in improving technologyusing ChatGPT-based mathematics learning in Junior High Schools (SMP). This study uses a qualitative approach with a case study design, which involves observation, interviews, and documentation to collect data from several junior high schools that apply SBM in mathematics learning. The collected data was analysed using thematic analysis techniques to identify patterns that emerged related to the application of SBM and technology in the learning process. The results show that applying SBM can increase the use of technology in mathematics learning, which contributes to improving the quality of learning. The contribution of this research is to provide new insights into the role of SBM in optimising the use of technologyusing ChatGPTto enhance the quality of mathematics learning in junior high schools.